2010
DOI: 10.1116/1.3455152
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and compression of an oligomer brush

Abstract: Self-assembled monolayers and oligomer brushes confined between two parallel plates show compressional forces that are nonmonotonic as a function of plate separation. In a realistic model of short alkanethiols, based on the rotationally isomeric state model with parameters from ab initio calculations, the authors show that nonmonotonic forces arise from the elimination of longer conformers as the distance between the plates is reduced. This nonmonotonicity is a size effect that disappears when the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, it has been also observed that polyelectrolytes may destabilize colloidal suspensions [42]. The problem of evaluation of the solvation forces between the surfaces modified with tethered charged chains and their dependence on the properties of a solvent and on the properties of the chains themselves was discussed in numerous papers [34,[43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been also observed that polyelectrolytes may destabilize colloidal suspensions [42]. The problem of evaluation of the solvation forces between the surfaces modified with tethered charged chains and their dependence on the properties of a solvent and on the properties of the chains themselves was discussed in numerous papers [34,[43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%